Workforce persuasion in digital transformation : a case study of a professional services firm - Basdew, Ivayran (My University, 2019)
While digital transformation is on top of many agendas, many organizations focus on transforming the business with new products, services, and operating models without regarding the workforce. How a new set course will affect the workforce is of high interest to leaders whose task it is to keep the workforce motivated. This research aims at strategies or approaches, which can be used by leaders who are trying to motivate their followers for digital transformation. The outcome is an answer to the question 'how do leaders motivate the workforce for changing working conditions resulting from digital transformation?’ A case study within a professional services firm with a foundation of literature within the domains of digital transformation and work motivation are the basis of this research. The qualitative findings are gathered by means of guided interviews where leaders within the company shared their perceptions on the disruptive nature of digital transformation on the working conditions and the nature of work. In addition, the leaders elaborated on how to approach the workforce in light of these findings. Analysis of the findings resulted in a multitude of approaches that are used to foster engagement, including envisioning, involvement, competition, guidance and support, and upskilling of the workforce. Further research from multiple perspectives is needed to come to a consensus about strategies. This research is a stepping-stone into a field of research regarding digital transformation and organizational behavior.
Keywords: Digital transformation, work motivation, transformational leadership